Enhanced piezoelectric output of NiO/nanoporous GaN by suppression of internal carrier screening. (8th May 2018) - Waseem, Aadil; Jeong, Dae Kyung; Johar, Muhammad Ali; Kang, Jin-Ho; Ha, Jun-Seok; Lee, June Key; Ryu, Sang-Wan
Abstract: The efficiency of piezoelectric nanogenerators (PNGs) significantly depends on the free carrier concentration of semiconductors. In the presence of a mechanical stress, piezoelectric charges are generated at both ends of the PNG, which are rapidly screened by the free carriers. The screening effect rapidly decreases the piezoelectric output within fractions of a second. In this study, the piezoelectric outputs of bulk- and nanoporous GaN-based heterojunction PNGs are compared. GaN thin films were epitaxially grown on sapphire substrates using metal organic chemical vapor deposition. Nanoporous GaN was fabricated using electrochemical etching, depleted of free carriers owing to the surface Fermi-level pinning. A highly resistive NiO thin film was deposited on bulk- and nanoporous GaN using radio frequency magnetron sputter. The NiO/nanoporous GaN PNG (NPNG) under a periodic compressive stress of 4 MPa exhibited an output voltage and current of 0.32 V and 1.48 μ A cm −2, respectively. The output voltage and current of the NiO/thin film-GaN PNG (TPNG) were three and five times smaller than those of the NPNG, respectively. Therefore, the high-resistivity of NiO and nanoporous GaN depleted by the Fermi-level pinning are advantageous and provide a better piezoelectric performance of the NPNG, compared with that of the TPNG.